Investigation of single phase reclosing using arc model on the 500 kV transmission line from Mae Moh to Tha Ta Ko - K. Ngamsanroaj (2018)
Single phase switching has become an increasingly more viable approach to the operation of EHV systems in recent years. Indeed, single phase reclosing, if successful, represents a significant step in improving system performance and is an attractive, economical means of obtaining acceptable transient stability with fewer lines. Single phase reclosing has the additional benefits of reducing switching overvoltages. This paper addresses the investigation of single phase reclosing using arc model on the on single and double circuit transmission line employing single phase switching due to single line to ground faults The work is performed by EMTP on the Thailand 500 kV transmission line from Mae Moh to Tha Ta Ko. A series of studies have been performed. © 2009 IEEE.